Technical & Financial Analysis Of Biomass Cogeneration Power Plant - Yanki Naidu, Ramesh (Universiti Sains Malaysia, 2005)
This report presents the technical and financial analysis of biomass cogeneration power plant. The term ‘biomass’ means any organic matter that is available on a renewable or recurring basis. Cogeneration means simultaneous generation of two different forms of useful energy using one single primary source. Technical and financial analysis (TFA) will be done using TFA model, version 2 from COGEN 3 software. This analysis was done on two different power plants. They are Sungei Dingin Palm Oil Mill (2 MWe plant), which implemented by the Kumpulan Guthrie Berhad, located in Kulim, Kedah and Rice Husk Fired Cogeneration Plant situated in Thailand. During the comparison on the different power plants been carried out, the analysis on technical and financial must take into account. The comparison between power plant using fresh fruit bunch and rice husk with the baseline or power plant using current energy supply also been carried out. TFA model is a pre-evaluation of cogeneration projects. It can calculate the financial performance of a cogeneration project compared to electricity purchase and thermal energy (steam/hot water) generation in boiler to the host facility.